2021
DOI: 10.1101/2021.04.17.21255471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Random glucose GWAS in 493,036 individuals provides insights into diabetes pathophysiology, complications and treatment stratification

Abstract: Homeostatic control of blood glucose requires different physiological responses in the fasting and post-prandial states. We reasoned that glucose measurements under non-standardised conditions (random glucose, RG) may capture diverse glucoregulatory processes more effectively than previous genome-wide association studies (GWAS) of fasting glycaemia or after standardised glucose loads. Through GWAS meta-analysis of RG in 493,036 individuals without diabetes of diverse ethnicities we identified 128 associated lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 104 publications
1
12
0
Order By: Relevance
“…10 It is interesting that a study found that the Gly168Ser variant does not alter the function of GLP1R. 18 However, previous reports in transfected Chinese hamster cell lines show that association of the 168Ser variant with reduced cell surface expression of the GLP1R and reduced intracellular calcium mobilisation following GLP1 stimulation. 19 The worse response seen with the Gly168Ser variant could also be due to reduced gene expression of GLP1R in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…10 It is interesting that a study found that the Gly168Ser variant does not alter the function of GLP1R. 18 However, previous reports in transfected Chinese hamster cell lines show that association of the 168Ser variant with reduced cell surface expression of the GLP1R and reduced intracellular calcium mobilisation following GLP1 stimulation. 19 The worse response seen with the Gly168Ser variant could also be due to reduced gene expression of GLP1R in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, relative GLP-1 resistance and impairment of the gut-brain GLP-1 axis has been described in preclinical studies. 14 Clinically, genetic variation in the GLP1R has been associated with changes in receptor signaling and glycemia 27 and differential responses to GLP-1RA in some human studies. 28,29 Variables such as local tissue expression of the GLP-1R, interindividual differences in GLP-1 receptor binding, receptor structure, or downstream signaling activity are difficult to measure in the context of large clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, as for Collinsella , we see a shared genetic link with genus in larger population based studies; in our recent report on genetics of random glucose in humans, we suggest that ABO/FUT2 genetic locus potentially orchestrates the correlation between Collinsella and the host glucose level [ 73 ]. Another piece of supporting evidence from a shared genetic background concerns family Peptococcaceae; rs7574352 associated with the family Peptococcaceae [ 39 ] is located in the intergenic region in the proximity (220kb apart) of IRF1 , which is involved in insulin resistance and susceptibility to T2DM, also suggested as a risk loci for PCOS [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 88%